Systemic and topical use of monoclonal antibodies to prevent the sexual transmission of HIV. (17th July 2017) - Anderson, Deborah J.; Politch, Joseph A.; Zeitlin, Larry; Hiatt, Andy; Kadasia, Kadryn; Mayer, Kenneth H.; Ruprecht, Ruth M.; Villinger, Francois; Whaley, Kevin J.
Abstract : N/A: Passive immunization, the transfer of antibodies to a nonimmune individual to provide immunological protection, has been used for over 100 years to prevent and treat human infectious diseases. The introduction of techniques to produce human mAbs has revolutionized the field, and a large number of human mAbs have been licensed for the treatment of cancer, autoimmune and inflammatory diseases. With the recent discovery and production of highly potent broadly neutralizing and other multifunctional antibodies to HIV, mAbs are now being considered for HIV therapy and prophylaxis. In this review, we briefly present recent advances in the anti-HIV mAb field and outline strategies for the selection, engineering and production of human mAbs, including the modification of their structure for optimized stability and function. We also describe results from nonhuman primate studies and phase 1 clinical trials that have tested the safety, tolerability, pharmacokinetics, and efficacy of mAb-based HIV prevention strategies, and discuss the future of parenteral and topical mAb administration for the prevention of HIV transmission.